2012
DOI: 10.1504/ijccm.2012.046031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cognitive diversity on relationship conflict, agreement-seeking behaviour and decision quality: a study of Chinese management teams

Abstract: Abstract:This study investigates (a) the effects of cognitive diversity on agreement seeking behaviour and relationship conflict, and (b) effects of agreement-seeking behaviour and relationship conflict on decision quality. Using structured survey instrument, this paper gathered data from 252 senior executives from mainland China and analysed the data using the regression techniques to test the hypotheses. The results support that cognitive diversity is positively related to relationship conflict and negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
3
2
0
2
Order By: Relevance
“…As part of the research, a survey was conducted with one respondent within the TMT of each organization. This is in line with previous research on TMTs (Parayitam et al , 2012; Janssen et al , 1999; Miller et al , 1998; Li and Li, 2009; Camelo-Ordaz et al , 2015) that contends that data from single respondents adequately represents the teams. It also builds on the assumption that respondents can accurately perceive themselves, others and their relationships with others, and that respondents do not have underlying motivations that would distort their responses (Parayitam et al , 2012).…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…As part of the research, a survey was conducted with one respondent within the TMT of each organization. This is in line with previous research on TMTs (Parayitam et al , 2012; Janssen et al , 1999; Miller et al , 1998; Li and Li, 2009; Camelo-Ordaz et al , 2015) that contends that data from single respondents adequately represents the teams. It also builds on the assumption that respondents can accurately perceive themselves, others and their relationships with others, and that respondents do not have underlying motivations that would distort their responses (Parayitam et al , 2012).…”
Section: Methodssupporting
confidence: 90%
“…This is in line with previous research on TMTs (Parayitam et al , 2012; Janssen et al , 1999; Miller et al , 1998; Li and Li, 2009; Camelo-Ordaz et al , 2015) that contends that data from single respondents adequately represents the teams. It also builds on the assumption that respondents can accurately perceive themselves, others and their relationships with others, and that respondents do not have underlying motivations that would distort their responses (Parayitam et al , 2012). To reduce the risk that social desirability would distort the responses, we emphasized the confidentiality and anonymity of the results to the study participants.…”
Section: Methodssupporting
confidence: 90%
“…The findings were exactly the opposite of what was proposed. Although this finding is consistent with some findings in the literature ( Jehn et al , 1997 , 1999 ) and is against the findings of some other studies, such as Parayitam et al (2012) , a more rigorous study of more recent literature provides a better insight into the reason for this finding.…”
Section: Discussionsupporting
confidence: 91%
“…Cognitive diversity, i.e. team-member perceptions also increase relationship conflict and decrease agreement-seeking behaviour as observed by Parayitam et al (2012). Liang et al (2007) found that knowledgediversity increases task conflict, which has a positive effect, but values-diversity increased relationship conflict, which reduced performance.…”
Section: Relationship Task Conflict Correlationmentioning
confidence: 78%